Lithium formate-based positive electrode lithium supplement material with high capacity and strong environmental stability, preparation method and application thereof, and deep sea energy storage battery
By using lithium formate and Kochen Black to prepare HLiCO2@ KB positive electrode lithium supplement material, the problem of insufficient lithium loss and energy density in lithium-ion batteries is solved, and the battery performance with high capacity and strong environmental stability is achieved, with wide application potential.
Patent Information
- Application Number
- CN202510246903.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-04
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-03-04
AI Technical Summary
The graphite-based anode of existing lithium-ion batteries consumes a large amount of active lithium when forming a solid electrolyte interface (SEI) film, resulting in insufficient Coulomb efficiency for the first time, reducing the energy density and cycle life of the battery. The volume of high-capacity negative electrode materials changes greatly during charging and discharging, further aggravating the lithium loss problem.
Lithium formate (HLiCO2) and Kochen Black (KB) were used as synthetic monomers, and HLiCO2@ KB positive electrode lithium supplement material was prepared by ball milling and spray drying. This material has a nano-scale core-shell structure, taking into account both conductivity and reactivity, and the process is simple and large-scale.
The positive electrode lithium supplement material with high capacity and strong environmental stability has been achieved, which has significantly improved the energy density and cycle life of lithium-ion batteries and has broad application potential, especially in the field of deep-sea energy storage batteries.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium formate-based positive electrode lithium supplement material with high capacity and strong environmental stability, a preparation method thereof, an application thereof, and a deep-sea energy storage battery. Background Art
[0002] Lithium-ion batteries (LIBs) are widely used in portable electronic devices and electric vehicles due to their high energy density and long cycle life. However, in the existing technology, the graphite-based anode of lithium-ion batteries consumes a large amount of active lithium when forming the solid electrolyte interface (SEI) film, accompanied by the side reaction decomposition of the electrolyte, resulting in insufficient first coulombic efficiency (about 90%-95%), which significantly reduces the energy density and cycle life of the battery. High-capacity anode materials (such as silicon, tin and phosphorus) further aggravate the lithium loss problem due to their large volume changes during charging and discharging (such as 420% for silicon, 260% for tin and 300% for phosphorus). As an important strategy, lithium supplementation technology can significantly improve the energy density of the battery by providing additional active lithium before cycling.
[0003] Traditional lithium supplementation methods include adding lithium powder, lithium foil or lithium-rich compounds, but these methods are limited by their high reactivity and strict environmental requirements. Organic lithium salts are ideal for lithium supplementation materials due to their low cost, excellent air stability and high theoretical capacity. Therefore, the present invention proposes a positive electrode lithium supplement based on lithium formate (HLiCO2) with a high theoretical capacity (510 mAh·g -1 ) and good air stability, low decomposition potential, and high application potential. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a lithium formate-based positive electrode lithium replenishing material with high capacity and strong environmental stability, and its preparation method, application and deep-sea energy storage battery. The method uses lithium formate (HLiCO2) and Ketjen black (KB) as synthetic monomers, combined with simple and scalable ball milling treatment, and then obtains a positive electrode lithium replenishing material with high capacity and strong environmental stability through subsequent spray drying, namely HLiCO2@KB positive electrode lithium replenishing material. The modification method of the electrode material has a simple process and high feasibility, and can realize large-scale production of positive electrode lithium replenishing materials with high capacity and strong environmental stability, thereby promoting the practical application of high-performance lithium-ion batteries, and has significant scientific value and broad practical application prospects.
[0005] The technical solution of the present invention is achieved in this way: A method for preparing a positive electrode lithium supplement material with high capacity and strong environmental stability, the preparation method comprising using lithium formate and Ketjen black in a mass ratio of 2-4:1-2 as synthetic monomers, ball milling, adding water for dispersion, and finally drying to obtain the positive electrode lithium supplement material.
[0006] Furthermore, it comprises lithium formate and Ketjen black in a mass ratio of 2 to 4:1.
[0007] Furthermore, based on the total weight of the synthetic monomers lithium formate and Ketjen black, the mass ratio of ball milling beads to lithium formate and Ketjen black is 1:1-1.5; the rotation speed of the ball milling treatment is 400-600 r / min, and the time is 5-8 h; before the ball milling treatment, the synthetic monomers are also ground, and the grinding time is 10-20 min.
[0008] Furthermore, in the ball milling process, the ratio of the number of small balls to large balls is 3-4:1; the particle size of the small balls is 1 mm, and the particle size of the large balls is 3 mm.
[0009] Furthermore, the drying includes high temperature spray drying, the drying temperature is 160-200°C, and the gas flow rate is 1-2 L·h -1 .
[0010] Furthermore, based on the total weight of the synthetic monomers lithium formate and Ketjen black, after ball milling, 20-40 mL of water is added to every 0.7-1 g of the total weight of the synthetic monomers for ultrasonic dispersion, and the ultrasonic dispersion time is 1-2 h; after the ultrasonic dispersion, stirring is also performed, and the stirring speed is 500-700 r / min for 10-16 h.
[0011] On the one hand, the present invention also provides a positive electrode lithium replenishing material with high capacity and strong environmental stability prepared by the above-mentioned preparation method of the positive electrode lithium replenishing material.
[0012] The present invention also provides a positive electrode sheet for a deep-sea energy storage battery, wherein the positive electrode sheet comprises the positive electrode lithium supplement material mentioned above.
[0013] The present invention also provides a deep-sea energy storage battery, which includes the above-mentioned positive electrode sheet.
[0014] On the other hand, the present invention also provides an application of a positive electrode lithium supplement material with high capacity and strong environmental stability, such as the application of the positive electrode lithium supplement material as a lithium supplement additive for a positive electrode of a lithium ion battery.
[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. Since the synthesized HLiCO2@KB positive electrode lithium supplement material is a nanoscale core-shell structure, it takes into account both conductivity and reactivity without affecting the crystallinity and high capacity of HLiCO2.
[0016] 2. The present invention has significant advantages such as low raw material cost, environmentally friendly process, high yield and large output, and exhibits excellent electrochemical performance. The method provides a general optimization strategy to significantly improve the energy density and cycle life of lithium-ion batteries. In the context of large-scale energy storage systems requiring excellent performance and high reliability, this high-capacity and environmentally stable positive electrode lithium supplement material shows wide application potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a SEM image of the positive electrode lithium supplement material (denoted as HLiCO2@KB) prepared in Example 1; Figure 2 TEM image of the positive electrode lithium supplement material (denoted as HLiCO2@KB) prepared in Example 1; Figure 3 The infrared spectra of the positive electrode lithium supplement material (referred to as HLiCO2@KB) and lithium formate (HLiCO2) prepared in Example 1; Figure 4 XRD spectrum of the positive electrode lithium supplement material (denoted as HLiCO2@KB) prepared in Example 1; Figure 5 The BET spectrum of the positive electrode lithium supplement material (denoted as HLiCO2@KB) prepared in Example 1; Figure 6 The EIS graph of a button-type lithium-ion half-cell assembled with the positive electrode lithium supplement material (denoted as HLiCO2@KB) and lithium formate (HLiCO2) prepared in Example 1; Figure 7 A comparison chart of the cycle performance of a button-type lithium-ion full battery at a rate of 0.5C, in which the positive electrode lithium supplement material (denoted as HLiCO2@KB) prepared in Example 1 is added to a lithium iron phosphate (LFPO) electrode and assembled with the lithium iron phosphate (LFPO) electrode; Figure 8 A comparison chart of the rate performance of a button-type lithium-ion full battery assembled by adding the positive electrode lithium supplement material (denoted as HLiCO2@KB) prepared in Example 1 into a lithium iron phosphate (LFPO) electrode (denoted as (LFPO@LCKB) electrode) and a lithium iron phosphate (LFPO) electrode; Fig. 9A comparison of the cycling performance of a button-type lithium-ion full battery assembled with a nickel-cobalt-manganese ternary material (NCM622) electrode and a nickel-cobalt-manganese ternary material (NCM622) electrode, wherein the positive electrode lithium supplement material (denoted as HLiCO2@KB) prepared in Example 1 is added to a nickel-cobalt-manganese ternary material (NCM622) electrode (denoted as (NCM622@LCKB) electrode, at a rate of 0.3C; Fig.10 A comparison of the cycling performance of a button-type lithium-ion full battery assembled with a nickel-cobalt-manganese ternary material (NCM622) electrode and a nickel-cobalt-manganese ternary material (NCM622) electrode, wherein the positive electrode lithium supplement material (denoted as HLiCO2@KB) prepared in Example 1 is added to a nickel-cobalt-manganese ternary material (NCM622) electrode (denoted as (NCM622@LCKB) electrode) at a rate of 1C; Fig.11 The rate performance comparison chart of the button-type lithium-ion full battery assembled with the nickel-cobalt-manganese ternary material (NCM622) electrode and the positive electrode lithium supplement material (denoted as HLiCO2@KB) prepared in Example 1 added into the nickel-cobalt-manganese ternary material (NCM622) electrode denoted as (NCM622@LCKB) electrode. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0019] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.
[0020] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.
[0021] In the agate ball milling beads of the embodiment of the present invention, the mass of the small ball with a particle size of 1 mm is 3.125 mg, and the mass of the large ball with a particle size of 3 mm is 84.75 mg.
[0022] Example 1 A method for preparing a positive electrode lithium replenishing material with high capacity and strong environmental stability, wherein the method uses lithium formate (HLiCO2) and Ketjen Black (KB) as synthetic monomers, combines a simple and scalable ball milling process, and then obtains a positive electrode lithium replenishing material with high capacity and strong environmental stability through subsequent spray drying, namely HLiCO2@KB positive electrode lithium replenishing material; the specific steps are as follows: 1) Add 0.6 g lithium formate and 0.3 g Ketjen black into an agate mortar and grind thoroughly for 20 min to obtain a black mixture; 2) The black mixed material obtained in step 1) is added into a nylon ball milling jar with a capacity of 100 mL and filled with agate ball milling beads, and 2 mL of anhydrous ethanol is added; wherein the particle sizes of the agate ball milling beads are 1 mm and 3 mm, respectively, the number ratio is 3:1, 10 large balls and 30 small balls; the ball milling speed is 500 rpm, and the time is 6 h; a black mixed material is obtained; 3) The black mixture obtained in step 2) was transferred to a 50 mL beaker, 40 mL of deionized water was added to the beaker, ultrasonicated for 1 h, and the beaker was placed on a magnetic stirrer with the speed set at 600 rpm. After stirring for 12 h, a black slurry was obtained; 4) The black slurry obtained in step 3) was transferred to a spray dryer and spray-dried at high temperature. The drying temperature was 180°C and the gas flow rate was 1 L·h -1 After cooling to room temperature, a positive electrode lithium replenishing material with high capacity and strong environmental stability is obtained.
[0023] The prepared positive electrode lithium supplement material (denoted as HLiCO2@KB) was subjected to morphological characterization and analysis.
[0024] like Figure 1 As shown, HLiCO2@KB is a sphere with a rough surface of amorphous carbon.
[0025] like Figure 2 As shown, HLiCO2@KB is a nanoscale core-shell structure, with the outer shell being amorphous carbon and the inner core being highly crystalline HLiCO2.
[0026] Depend on Figure 3 It can be concluded that the KB coated on the outside of HLiCO2 does not destroy the crystal structure of HLiCO2 itself.
[0027] Depend on Figure 4 It can be found that the XRD spectrum of HLiCO2@KB corresponds to the standard XRD card of HLiCO2, and it can also be concluded that the KB coated on the outside of HLiCO2 does not destroy the crystal structure of HLiCO2 itself. Depend on Figure 5 It can be seen that HLiCO2@KB has a very large specific surface area.
[0028] Example 2 The positive electrode lithium supplement material with high capacity and strong environmental stability obtained in the above Example 1 is used to assemble a button-type lithium ion half-cell, and the material is added as a lithium supplement additive to a lithium iron phosphate (LFPO) electrode and a nickel-cobalt-manganese ternary material (NCM622) electrode to assemble a button-type lithium ion full battery, as follows: (1) The positive electrode lithium supplement material (denoted as HLiCO2@KB) prepared by the present invention is used as a positive electrode active material for a lithium ion battery, conductive carbon black is used as a conductive agent, and polyvinylidene fluoride is used as a binder; the mass ratio of the active material, the conductive agent, and the binder is 6:3:1, and they are mixed in proportion and N-methylphthalimide is added to prepare a slurry, which is evenly coated on an aluminum foil.
[0029] (2) The positive electrode lithium supplement material (denoted as HLiCO2@KB) prepared in Example 1 of the present invention is added to lithium iron phosphate (LFPO) at a ratio of 10% as a positive electrode active material for a lithium ion battery, conductive carbon black is used as a conductive agent, and polyvinylidene fluoride is used as a binder; the mass ratio of the active material, the conductive agent, and the binder is 7:2:1. After they are mixed in proportion, N-methylphthalimide is added to make a slurry, which is evenly coated on an aluminum foil.
[0030] (3) The positive electrode lithium supplement material prepared in Example 1 of the present invention (denoted as HLiCO2@KB) was added to the nickel-cobalt-manganese ternary material (NCM622) at a ratio of 10% as a positive electrode active material for a lithium-ion battery, conductive carbon black was used as a conductive agent, and polyvinylidene fluoride was used as a binder; the mass ratio of the active material, the conductive agent, and the binder was 8:1:1. After they were mixed in proportion, N-methylphthalimide was added to form a slurry, which was evenly coated on an aluminum foil.
[0031] (4) In the present invention, graphite is used as the negative electrode active material of the lithium ion full battery, conductive carbon black is used as the conductive agent, and polyvinylidene fluoride is used as the binder; the mass ratio of the active material, the conductive agent, and the binder is 91.6:1.8:6.6. After they are mixed in proportion, N-methylphthalimide is added to make a slurry, which is evenly coated on a copper foil.
[0032] (5) The positive electrode sheet is made by punching aluminum foil into a 10 mm diameter disc. The mass loading of the punched electrode sheet is 1.6-2.4 mg / cm -2 .
[0033] (6) The positive electrode sheet is made by punching copper foil into a 10 mm diameter disc. The mass loading of the punched electrode sheet is 0.8-1.2 mg / cm -2 .
[0034] (7) CR2016 button cells were assembled in an argon glove box, with polypropylene (PP) as the separator; the lithium ion electrolyte was 1 M LiPF6 dissolved in a solvent mixture of ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 3:7.
[0035] 1. Replace the positive electrode lithium supplement material (denoted as HLiCO2@KB) with lithium formate (HLiCO2) and assemble it with lithium foil into a button-type lithium-ion battery in the same way as above.
[0036] Comparison of the EIS graphs of two button lithium-ion batteries Figure 6 As shown: It can be seen that the impedance of the lithium-ion battery assembled with the positive electrode lithium supplement material (referred to as HLiCO2@KB) is lower. It is proved that compared with the synthetic monomer lithium formate (HLiCO2), the positive electrode lithium supplement material (referred to as HLiCO2@KB) prepared by the present invention has higher conductivity and electrochemical activity.
[0037] 2. Lithium iron phosphate (LFPO) with added positive lithium supplement material (denoted as HLiCO2@KB) is denoted as LFPO@LCKB positive electrode and lithium iron phosphate (LFPO) positive electrode are respectively assembled with graphite negative electrode into button lithium-ion batteries. The two lithium-ion full batteries are denoted as Gr||LFPO@LCKB and Gr||LFPO respectively.
[0038] Comparison of the cycling performance of two button-type lithium-ion batteries at a rate of 0.5C. Figure 7 As shown: The initial charge capacity of the Gr||LFPO full battery is 143.82 mAh g -1 , while the initial discharge capacity is only 113.36 mAh·g -1 This is because some active lithium ions are consumed in the process of forming SEI film on the graphite surface without being replenished.
[0039] The initial charge capacity of the complete Gr||LFPO@LCKB full cell is 155.01 mAh g -1 Since HLiCO2@KB decomposition can provide additional active lithium, the discharge capacity is 128.74 mAh·g -1 , an increase of 15.33 mAh g -1 In the 100-cycle cycle, the discharge capacity of the Gr||LFPO@LCKB full battery is significantly higher than that of the Gr||LFPO full battery. This proves that adding positive electrode lithium supplement material (denoted as HLiCO2@KB) can significantly improve the capacity of lithium iron phosphate (LFPO) full batteries.
[0040] 3. Lithium iron phosphate (LFPO) with added positive lithium supplement material (denoted as HLiCO2@KB) is denoted as LFPO@LCKB positive electrode and lithium iron phosphate (LFPO) positive electrode are respectively assembled with graphite negative electrode into button lithium-ion batteries. The two lithium-ion full batteries are denoted as Gr||LFPO@LCKB and Gr||LFPO respectively.
[0041] Comparison of rate performance of two button lithium-ion batteries Figure 8As shown in Figure 2, when the rate gradually increases from 0.1C to 0.2C, 0.5C, 1C, 2C, and 5C, the discharge specific capacities of the Gr||LFPO@LCKB full battery are 136.36, 130.61, 124.41, 114.85, 98.55, and 77.8 mAh·g, respectively. -1 The discharge specific capacities of Gr||LFPO full batteries are 127.64, 122.11, 115.22, 104.64, 71.83, and 43.66 mAh·g, respectively. -1 When the current density is 2C, the capacity of Gr||LFPO@LCKB full battery is much higher than that of Gr||LFPO full battery. It is proved that adding positive electrode lithium supplement material (denoted as HLiCO2@KB) can significantly improve the rate performance of lithium iron phosphate (LFPO) full battery.
[0042] 4. The nickel-cobalt-manganese ternary material (NCM622) with added positive lithium supplement material (denoted as HLiCO2@KB) is denoted as NCM622@LCKB positive electrode and the nickel-cobalt-manganese ternary material (NCM622) positive electrode is assembled with graphite negative electrode into button-type lithium-ion batteries. The two lithium-ion full batteries are denoted as Gr||NCM622@LCKB and Gr||NCM622 respectively.
[0043] Comparison of the cycling performance of two button lithium-ion batteries at a rate of 0.3C. Fig. 9 As shown: The initial charge capacity of the Gr||NCM622 full battery is 204.69 mAh g -1 , while the initial discharge capacity is only 162.59 mAh·g -1 This is because some active lithium ions are consumed in the process of forming SEI film on the graphite surface without being replenished.
[0044] The initial charge capacity of the complete Gr||NCM622@LCKB full cell is 238.65 mAh g -1 , and because HLiCO2@KB decomposition can provide additional active lithium, the discharge capacity is 176.03 mAh·g -1 , an increase of 13.97 mAh g -1 In the 100-cycle cycle, the discharge capacity of the Gr||NCM622@LCKB full battery is significantly higher than that of the Gr||NCM622 full battery. This proves that adding positive electrode lithium supplement material (denoted as HLiCO2@KB) can significantly improve the capacity of the nickel-cobalt-manganese ternary material (NCM622) full battery.
[0045] 5. The nickel-cobalt-manganese ternary material (NCM622) with added positive lithium supplement material (denoted as HLiCO2@KB) is denoted as NCM622@LCKB positive electrode and the nickel-cobalt-manganese ternary material (NCM622) positive electrode is assembled with graphite negative electrode into button-type lithium-ion batteries. The two lithium-ion full batteries are denoted as Gr||NCM622@LCKB and Gr||NCM622 respectively.
[0046] Comparison of the cycling performance of two button-type lithium-ion batteries at a rate of 1C. Fig.10 As shown: The initial charge capacity of the Gr||NCM622 full battery is 166.8 mAh g -1 , while the initial discharge capacity is only 124.73 mAh·g -1 This is because some active lithium ions are consumed in the process of forming SEI film on the graphite surface without being replenished.
[0047] The initial charge capacity of the complete Gr||NCM622@LCKB full cell is 192.96 mAh g -1 , and because HLiCO2@KB decomposition can provide additional active lithium, the discharge capacity is 145 mAh·g -1 , an increase of 20.27 mAh g -1 In the 300-cycle cycle, the discharge capacity of the Gr||NCM622@LCKB full battery is significantly higher than that of the Gr||NCM622 full battery. This proves that adding positive electrode lithium supplement material (denoted as HLiCO2@KB) can significantly improve the capacity of the nickel-cobalt-manganese ternary material (NCM622) full battery.
[0048] 6. The nickel-cobalt-manganese ternary material (NCM622) with added positive lithium supplement material (denoted as HLiCO2@KB) is denoted as NCM622@LCKB positive electrode and the nickel-cobalt-manganese ternary material (NCM622) positive electrode is assembled with graphite negative electrode into button-type lithium-ion batteries. The two lithium-ion full batteries are denoted as Gr||NCM622@LCKB and Gr||NCM622 respectively.
[0049] Comparison of rate performance of two button lithium-ion batteries Fig.11 As shown in Figure 2, when the rate increases from 0.1C to 0.2C, 0.3C, 0.5C, 1C, and 2C, the discharge specific capacities of the Gr||NCM622@LCKB full battery are 179.81, 170.11, 159.73, 149.09, 133.63, and 112.86 mAh·g, respectively. -1 The discharge specific capacities of Gr||NCM622 full batteries are 170.96, 149.79, 127.1, 102.37, 68.92, and 27.12 mAh·g -1When the current density is 0.2C, the capacity of Gr||NCM622@LCKB full battery is much higher than that of Gr||NCM622 full battery. It is proved that adding positive electrode lithium supplement material (denoted as HLiCO2@KB) can significantly improve the rate performance of nickel-cobalt-manganese ternary material (NCM622).
[0050] From the above, it can be seen that the positive electrode lithium replenishing material with high capacity and strong environmental stability prepared in Example 1 of the present invention has a nanoscale core-shell structure, with an outer shell of amorphous carbon and an inner core of high crystallinity HLiCO2, and a smaller particle size, which solves the challenge of balancing high capacity and electronic conductivity in the material optimization process; the modification method of the positive electrode lithium replenishing material has a simple process and high feasibility, and can realize large-scale production of positive electrode lithium replenishing materials with high capacity and strong environmental stability, thereby promoting the practical application of high-performance lithium-ion batteries, indicating that the positive electrode lithium replenishing material with high capacity and strong environmental stability prepared by the present invention has the potential to prepare deep-sea energy storage batteries.
[0051] Example 3 A method for preparing a positive electrode lithium replenishing material with high capacity and strong environmental stability, wherein the method uses lithium formate (HLiCO2) and Ketjen black (KB) as synthetic monomers, combines a simple and scalable ball milling process, and then obtains a positive electrode lithium replenishing material with high capacity and strong environmental stability through subsequent spray drying, namely HLiCO2@KB positive electrode lithium replenishing material; the specific steps are as follows: 1) Add 0.6 g lithium formate and 0.2 g Ketjen black into an agate mortar and grind thoroughly for 20 min to obtain a black mixture; 2) The black mixed material obtained in step 1) is added into a nylon ball milling jar with a capacity of 100 mL and filled with agate ball milling beads, and 2 mL of anhydrous ethanol is added; wherein the particle sizes of the agate ball milling beads are 1 mm and 3 mm, respectively, the number ratio is 3:1, 10 large balls and 30 small balls; the ball milling speed is 500 rpm, and the time is 6 h; a black mixed material is obtained; 3) The black mixture obtained in step 2) was transferred to a 50 mL beaker, 40 mL of deionized water was added to the beaker, ultrasonicated for 1 h, and the beaker was placed on a magnetic stirrer with the speed set at 600 rpm. After stirring for 12 h, a black slurry was obtained; 4) The black slurry obtained in step 3) was transferred to a spray dryer and spray-dried at high temperature. The drying temperature was 180°C and the gas flow rate was 1 L·h -1 After cooling to room temperature, a positive electrode lithium replenishing material with high capacity and strong environmental stability is obtained.
[0052] Example 4 A method for preparing a positive electrode lithium replenishing material with high capacity and strong environmental stability, wherein the method uses lithium formate (HLiCO2) and Ketjen black (KB) as synthetic monomers, combines a simple and scalable ball milling process, and then obtains a positive electrode lithium replenishing material with high capacity and strong environmental stability through subsequent spray drying, namely HLiCO2@KB positive electrode lithium replenishing material; the specific steps are as follows: 1) Add 0.6 g lithium formate and 0.3 g Ketjen black into an agate mortar and grind thoroughly for 20 min to obtain a black mixture; 2) The black mixed material obtained in step 1) is added into a nylon ball milling jar with a capacity of 100 mL and filled with agate ball milling beads, and 2 mL of anhydrous ethanol is added; wherein the particle sizes of the agate ball milling beads are 1 mm and 3 mm, respectively, the number ratio is 3:1, 10 large balls and 30 small balls; the ball milling speed is 500 rpm, and the time is 6 h; a black mixed material is obtained; 3) The black mixture obtained in step 2) was transferred to a 50 mL beaker, 30 mL of deionized water was added to the beaker, ultrasonicated for 1 h, and the beaker was placed on a magnetic stirrer with the speed set at 600 rpm. After stirring for 12 h, a black slurry was obtained; 4) The black slurry obtained in step 3) was transferred to a spray dryer and spray-dried at high temperature. The drying temperature was 180°C and the gas flow rate was 1 L·h -1 After cooling to room temperature, a positive electrode lithium replenishing material with high capacity and strong environmental stability is obtained.
[0053] Example 5 A method for preparing a positive electrode lithium replenishing material with high capacity and strong environmental stability, wherein the method uses lithium formate (HLiCO2) and Ketjen black (KB) as synthetic monomers, combines a simple and scalable ball milling process, and then obtains a positive electrode lithium replenishing material with high capacity and strong environmental stability through subsequent spray drying, namely HLiCO2@KB positive electrode lithium replenishing material; the specific steps are as follows: 1) Add 0.6 g lithium formate and 0.3 g Ketjen black into an agate mortar and grind thoroughly for 20 min to obtain a black mixture; 2) The black mixed material obtained in step 1) is added into a nylon ball milling jar with a capacity of 100 mL and filled with agate ball milling beads, and 2 mL of anhydrous ethanol is added; wherein the particle sizes of the agate ball milling beads are 1 mm and 3 mm, respectively, the number ratio is 3:1, 10 large balls and 30 small balls; the ball milling speed is 500 rpm, and the time is 6 h; a black mixed material is obtained; 3) The black mixture obtained in step 2) was transferred to a 50 mL beaker, 20 mL of deionized water was added to the beaker, ultrasonicated for 1 h, and the beaker was placed on a magnetic stirrer, the speed was set to 600 rpm, and stirred for 12 h to obtain a black slurry; 4) The black slurry obtained in step 3) was transferred to a spray dryer and spray-dried at high temperature. The drying temperature was 180°C and the gas flow rate was 1 L·h -1 After cooling to room temperature, a positive electrode lithium replenishing material with high capacity and strong environmental stability is obtained.
[0054] The above is a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.
Claims
1. A method for preparing a positive electrode lithium supplement material with high capacity and strong environmental stability, characterized in that: The preparation method comprises using lithium formate and Ketjen black in a mass ratio of 2-4:1-2 as synthetic monomers, performing ball milling, adding water for dispersion, and finally drying to obtain the positive electrode lithium supplement material; Based on the total weight of the synthetic monomer, after ball milling, 20-40 mL of water is added to every 0.7-1 g of the total weight of the synthetic monomer for ultrasonic dispersion, and the ultrasonic dispersion time is 1-2 h; The drying includes high temperature spray drying, the drying temperature is 160-200°C, and the gas flow rate is 1-2 L·h -1 .
2. The method for preparing a positive electrode lithium supplement material according to claim 1, characterized in that: It comprises lithium formate and Ketjen black in a mass ratio of 2 to 4:
1.
3. The method for preparing a positive electrode lithium supplement material according to claim 1, characterized in that: The ball-to-material mass ratio is 1:1-1.5 based on the total weight of the synthetic monomer; the rotation speed of the ball milling treatment is 400-600 r / min, and the time is 5-8 h; before the ball milling treatment, the synthetic monomer is also ground, and the grinding time is 10-20 min.
4. The method for preparing a positive electrode lithium supplement material according to claim 3, characterized in that: In the ball milling process, the ratio of the number of small balls to that of large balls is 3-4:1; the particle size of the small balls is 1 mm, and the particle size of the large balls is 3 mm.
5. The method for preparing a positive electrode lithium supplement material according to claim 1, characterized in that: The ultrasonic dispersion is followed by stirring, wherein the stirring speed is 500-700 r / min and the stirring time is 10-16 h.
6. A positive electrode lithium replenishing material with high capacity and strong environmental stability prepared by the preparation method of the positive electrode lithium replenishing material according to any one of claims 1 to 5.
7. A positive electrode sheet for a deep-sea energy storage battery, characterized in that: The positive electrode sheet includes the positive electrode lithium supplement material according to claim 6.
8. A deep-sea energy storage battery, characterized in that: The deep-sea energy storage battery comprises the positive electrode sheet as described in claim 7.
9. Application of a positive electrode lithium supplement material with high capacity and strong environmental stability, characterized in that: The positive electrode lithium supplement material as described in any one of claims 1 to 5 includes use as a lithium supplement additive for the positive electrode of a lithium-ion battery.
Citation Information
Patent Citations
Composite lithium supplementing material and preparation method thereof, lithium supplementing coating and preparation method thereof, and lithium battery
CN116799210A
Composite lithium supplementing material, preparation method thereof and battery
CN118299578A
Positive electrode lithium supplement additive and preparation method and application thereof
CN118522973A
Lithium supplemental material, preparation method therefor and use thereof
EP4120398A1